2006
DOI: 10.1007/s11182-006-0265-8
|View full text |Cite
|
Sign up to set email alerts
|

Technique of synthesis and optical properties of CdS/polymethylmethacrylate nanocomposites

Abstract: The technique of synthesis of polymethylmethacrylate -cadmium sulfide nanocomposites involving precipitation of CdS nanoparticles from polymethylmethacrylate solution in methylmethacrylate monomer with its subsequent polymerization is presented. The influence of molecular polymer mass and polymerization conditions on the dispersion stability is discussed. The spectral-luminescent properties of nanocomposites are investigated. A difference between the spectral-luminescent properties of the surface composite lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…We note that the macromolecules of transparent PMMA are capable of stabilizing the CdS nanoparticles synthesized in the medium of the MMA monomer, and their size depends on the molecular mass of the polymer [153]. The nanodimensional CdS is capable of initiating the polymerization of vinyl monomers under the influence of UV light.…”
Section: Methods Of Introduction Of Dyes Into the Polymer And Their Cmentioning
confidence: 91%
“…We note that the macromolecules of transparent PMMA are capable of stabilizing the CdS nanoparticles synthesized in the medium of the MMA monomer, and their size depends on the molecular mass of the polymer [153]. The nanodimensional CdS is capable of initiating the polymerization of vinyl monomers under the influence of UV light.…”
Section: Methods Of Introduction Of Dyes Into the Polymer And Their Cmentioning
confidence: 91%
“…In [15] it was demonstrated that macromolecules of optically transparent polymer -polymethylmethacrylate (PMMA) -can stabilize cadmium sulfide nanoparticles synthesized in a methylmethacrylate (MMA) medium. Moreover, the rate of particle aggregation depends on the molecular mass of the polymer: PMMA molecules with short chains have higher stabilizing ability.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the rate of particle aggregation depends on the molecular mass of the polymer: PMMA molecules with short chains have higher stabilizing ability. A method of one-step, size-controlled synthesis of CdS/PMMA nanocomposites was suggested in [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations